Positive electrode active material, method for producing lithium supplementing additive, and battery cell

CN122992068APending Publication Date: 2026-10-27BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611152946.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

Smart Images

  • Figure CN122992068A_ABST
    Figure CN122992068A_ABST
Patent Text Reader

Abstract

The application discloses a positive electrode active material, a preparation method of a lithium supplementing additive, a battery monomer, and the battery monomer comprises a positive electrode sheet, a negative electrode current collector, an electrolyte and a separator arranged between the positive electrode sheet and the negative electrode current collector; the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector, the positive electrode film layer comprises a positive electrode active material and a lithium supplementing additive, the positive electrode active material comprises O2 phase lithium cobalt oxide, and the lithium supplementing additive comprises a lithium-rich cobalt-based oxide. Thus, the application introduces O2 phase lithium cobalt oxide as a main lithium storage framework, which has a high working voltage, a high capacity and a relatively optimal structural stability, is beneficial to improving the structural stability of the positive electrode active material under a high voltage and a deep lithium extraction state, relieving irreversible phase transition in a deep lithium extraction process, and the lithium supplementing additive has a high capacity release and a relatively optimal stability, can effectively compensate for irreversible lithium loss in a cycle process, and prolongs the cycle life of a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of negative electrode-free lithium metal battery technology, specifically to the preparation method of positive electrode active material, lithium supplementation additive, and battery cell. Background Technology

[0002] With the increasing demands for battery energy density from portable electronic devices, electric vehicles, and energy storage systems, traditional lithium-ion batteries are gradually approaching their theoretical energy density limit. Anode-less batteries, as a novel high-energy-density battery system, do not pre-place negative electrode active materials such as graphite, silicon-carbon, or metallic lithium in their initial assembly state. Instead, they use current collectors such as copper foil as the negative electrode current collector. During charging, lithium ions released from the positive electrode are deposited in situ on the surface of the negative electrode current collector to form a lithium metal negative electrode. Therefore, this significantly reduces the mass and volume ratio of inactive materials on the negative electrode side, thereby increasing the battery's energy density and showing significant application potential.

[0003] It should be noted that the above statements are only used to provide background information related to this application and do not necessarily constitute prior art. Summary of the Invention

[0004] In a first aspect of this application, a battery cell is provided, comprising a positive electrode, a negative current collector, an electrolyte, and a separator disposed between the positive electrode and the negative current collector; the positive electrode comprises a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer comprising a positive electrode active material and a lithium supplementation additive, the positive electrode active material comprising O2 phase lithium cobalt oxide, and the lithium supplementation additive comprising lithium-rich cobalt-based oxide; the XRD pattern of the mixture of the positive electrode active material and the lithium supplementation additive has a first diffraction peak and a second diffraction peak, the peak position of the first diffraction peak is 18.35°~18.75°, the peak position of the second diffraction peak is 23.2°~23.6°, and the peak intensity ratio Q1 of the peak intensity I2 of the second diffraction peak and the peak intensity I1 of the first diffraction peak is 0.8%~10.5%. Therefore, this application introduces O2-phase lithium cobalt oxide as the main lithium storage framework, which has a high operating voltage, high capacity, and superior structural stability. This is beneficial for improving the structural stability of the cathode active material under high voltage and deep delithiation conditions, mitigating irreversible phase transitions during deep delithiation. Simultaneously, the lithium replenishment additive used exhibits high capacity utilization and superior stability, effectively compensating for irreversible lithium loss during cycling and extending battery cycle life. Furthermore, when the peak intensity ratio meets the aforementioned range, it indicates that the addition amounts of lithium replenishment additive and cathode active material are moderate, sufficiently compensating for irreversible lithium loss caused by initial lithium metal deposition, interface film formation, and dead lithium generation. At the same time, excessive introduction of lithium replenishment additive will not lead to a decrease in the proportion of cathode active material, thus contributing to improved battery energy density.

[0005] In some embodiments, Q1 is 2.0% to 8.4%. This is beneficial for further improving the energy density of the battery.

[0006] In some embodiments, the delithiation plateau of the lithium replenishment additive is 3.3 V to 3.7 V, and the delithiation plateau of the positive electrode active material is not less than 3.7 V, optionally 3.7 V to 4.6 V. Thus, a suitable potential gap exists between the lithium replenishment additive and the positive electrode active material, reducing the likelihood of side reactions between them. If the delithiation plateau of the lithium replenishment additive is too high, the lithium replenishment process must occur after the positive electrode active material has entered a higher voltage and deeper delithiation state. In this case, the lithium replenishment process is prone to superimposed on the high-voltage interface instability process of the positive electrode active material. Furthermore, an appropriate potential difference promotes a good functional division of labor between the two within the capacity contribution range, with the lithium replenishment additive preferentially undergoing delithiation before the positive electrode active material. This allows the initial lithium deposition and interface film construction in the anode-free system to preferentially occur within the relatively mild positive electrode potential range. This reduces the risk of lithium ion nucleation and deposition on the surface of the anode current collector, rapid SEI formation, and high-delithiation interface side reactions of the positive electrode active material occurring at the same stage.

[0007] In some embodiments, the median particle size of the mixture of the positive electrode active material and the lithium supplementation additive is 15.6 μm to 17.8 μm.

[0008] In some embodiments, the median particle size of the positive electrode active material is 16 μm to 18 μm; and / or, the median particle size of the lithium supplementation additive is 7 μm to 8 μm.

[0009] After mixing the positive electrode active material and the lithium supplement additive, a particle size distribution is formed with the larger-diameter positive electrode active material as the main component and the smaller-diameter lithium supplement additive distributed in the interparticle spaces. Based on this, the median particle size of the mixture is further limited to 15.6 μm~17.8 μm. This ensures that the mixed particle system maintains the main framework formed by the positive electrode active material while avoiding significant agglomeration or segregation of the lithium supplement additive, thus matching the particle size of each component with the overall particle size distribution after mixing. This combination improves the dispersion uniformity and packing density of the mixed powder. Simultaneously, it reduces local enrichment or insufficient distribution of the lithium supplement additive, improves slurry stability, coating uniformity, and electrode compaction performance, and promotes the uniform release of active lithium during the first charging process, reducing local polarization, excessive lithium supplementation, and interfacial side reactions.

[0010] In some embodiments, the chemical formula of the positive electrode active material is LiCo. p M qO2, wherein M includes at least one of Zn, Ni, Mg, Cu, and Ca, 0.9≤p≤1.0, 0≤q≤0.1, and p+q=1.0. Therefore, doping with element M helps improve the cycle stability of the positive electrode active material under high voltage.

[0011] In some embodiments, the lithium supplementation additive comprises a matrix and a manganese-based oxide located on at least a portion of the surface of the matrix, the matrix having the chemical formula Li. x Co y E z O4, wherein E includes at least one of Zn, Mg, Cu, and Ca, 5.9≤x≤6.15, 0.9≤y≤1.0, 0≤z≤0.1, and y+z=1.0. Therefore, manganese-based oxides can stabilize the surface of lithium-replenishing additives, effectively improving their environmental stability while mitigating side reactions such as reactive oxygen release and electrolyte oxidation decomposition during the first charging process, thus reducing unnecessary consumption of active lithium. Furthermore, manganese-based oxides possess certain variable valence state characteristics, which, under controlled conditions, can assist in constructing an interfacial environment conducive to lithium nucleation, reducing the tendency for uneven local deposition on the negative electrode side.

[0012] In some embodiments, the manganese-based oxide includes at least one selected from MnO, Mn2O3, Mn3O4, MnO2, LiMnO2, Li2MnO3, and LiMn2O4. This helps to further improve the air stability of the lithium supplementation additive, reduce unnecessary consumption of active lithium, and decrease the tendency for uneven local deposition on the negative electrode side.

[0013] In some embodiments, the mass content of Mn element in the mixture of the positive electrode active material and the lithium supplementation additive is 0.0005wt% to 0.1wt%, optionally 0.001% to 0.077%. This helps to construct an interfacial environment conducive to lithium metal nucleation and reduces the tendency for uneven local deposition on the negative electrode side.

[0014] In some embodiments, the XRD pattern of the lithium-supplementing additive has a third diffraction peak, and the peak intensity ratio Q2 of the third diffraction peak I3 to the peak intensity I2 of the second diffraction peak satisfies 0 < Q2 ≤ 3.5%, where Q2 can be selected from 0.5% to 3.0%. Therefore, the moderate coating amount of manganese-based oxide on the surface of the lithium-supplementing additive helps to construct an interface environment conducive to lithium metal nucleation and reduces the tendency for uneven local deposition on the negative electrode side.

[0015] In some embodiments, the mass fraction of the manganese-based oxide in the lithium replenishing additive is 0.1% to 4.3%. This helps to improve the interfacial stability of the lithium replenishing additive and reduce the occurrence of side reactions such as the release of reactive oxygen species and the oxidative decomposition of the electrolyte during the first charging process.

[0016] In some embodiments, the mass fraction of the positive electrode active material in the positive electrode film is 90% to 97%. This is beneficial for improving the battery's capacity utilization and cycle stability.

[0017] In some embodiments, the mass ratio of the lithium replenishing additive to the positive electrode active material in the positive electrode film layer is (0.5~5):100, optionally (1~4):100. Therefore, by adding an appropriate amount of lithium replenishing additive, irreversible lithium loss caused by initial lithium metal deposition, interface film formation, and dead lithium generation can be fully compensated; at the same time, excessive introduction of lithium replenishing additive will not lead to a decrease in the proportion of positive electrode active material, which is beneficial to improving the energy density of the battery.

[0018] In some embodiments, the positive electrode film further includes a conductive agent and a binder; wherein the conductive agent includes at least one selected from carbon nanotubes, graphene, acetylene black, and Ketjen black; and the binder includes at least one selected from polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, and styrene-butadiene rubber. This improves the conductivity of the positive electrode film.

[0019] In some embodiments, the negative electrode current collector includes at least one of copper foil, carbon-coated copper foil, and perforated copper foil. This helps to enhance the affinity for lithium, reduce interfacial resistance, decrease local current density, make lithium ion distribution more uniform, and suppress lithium dendrite growth.

[0020] In some embodiments, the membrane comprises a ceramic particle-modified polyethylene microporous membrane. This improves the mechanical strength of the membrane and effectively resists lithium dendrite penetration.

[0021] In a second aspect of this application, a method for preparing the aforementioned positive electrode active material is proposed, comprising: mixing a cobalt source, a sodium source, and optionally an M source, and then sintering the mixture under an oxygen atmosphere; crushing and sieving the mixture to obtain a P2 phase precursor; immersing the P2 phase precursor in a mixed aqueous solution of LiCl and LiOH for reaction; subsequently filtering, washing, and drying to obtain the positive electrode active material, wherein the positive electrode active material is an O2 phase lithium cobalt oxide. This method helps to obtain a positive electrode active material with high capacity and structural stability, and the preparation method is simple, easy to operate, and readily applicable to industrial production.

[0022] In some embodiments, at least one of the following conditions is met: The cobalt source includes at least one of cobalt tetroxide, cobalt hydroxide, cobalt sulfide, cobalt nitrate, cobalt sulfate, and cobalt hydroxyoxide. The sodium source includes at least one of sodium carbonate, sodium bicarbonate, and sodium hydroxide; The ratio z of the molar amounts of sodium in the sodium source to the sum of the molar amounts of cobalt in the cobalt source and M in the M source is n(Na):n(Co+M), 0.7≤z<1; The M source includes at least one of the oxides and hydroxides corresponding to the M element; The concentration of the mixed aqueous solution of LiCl and LiOH is 1.0 mol / L to 3.0 mol / L; The reaction time is 20-30 hours, and the temperature is 100°C. The drying temperature is 50℃~90℃.

[0023] Meeting the above conditions helps to prepare positive electrode active materials with stable structure, high purity, and appropriate particle size.

[0024] In some embodiments, the sintering temperature is 700℃~800℃, and the holding time is 40h~50h. This helps to synthesize a high-purity, structurally stable P2 phase precursor.

[0025] In a third aspect, this application proposes a method for preparing the aforementioned lithium-replenishing additive, comprising: mixing a lithium source, a cobalt source, and optionally an E source, and then performing a first sintering treatment under an inactive atmosphere; followed by crushing and sieving to obtain a matrix; mixing the matrix with a manganese source and then performing a second sintering treatment under an inactive atmosphere to form manganese-based oxides on a portion of the surface of the matrix; and finally, crushing and sieving to obtain the lithium-replenishing additive. Thus, this application obtains a lithium-replenishing additive with high air stability by coating a matrix surface with manganese-based oxides.

[0026] In some embodiments, at least one of the following conditions is met: The lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, and lithium chloride; The cobalt source includes at least one of cobalt oxide and cobalt hydroxide; The E source includes at least one of the oxides and hydroxides corresponding to the element E; The manganese source includes at least one of MnO, Mn2O3, Mn3O4, and MnO2; The ratio of the molar amounts of lithium in the lithium source to the sum of the molar amounts of cobalt in the cobalt source and E in the E source, n(Li):n(Co+E), is (5.9~6.15):1; The temperature of the first sintering treatment is 500℃~1000℃, and the time is 8h~24h; The second sintering treatment is performed at a temperature of 300℃ to 700℃ for 5 hours to 10 hours.

[0027] Meeting the above conditions helps to form a dense and uniform manganese-based oxide on the substrate surface, which in turn helps to improve the air stability of the lithium supplement additive. Attached Figure Description

[0028] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, wherein, Figure 1 The XRD pattern of a mixture of positive electrode active material and lithium supplementation additive according to an embodiment of this application; Figure 2 The XRD pattern of a lithium supplement additive according to one embodiment of this application is shown. Figure 3 This is an XRD pattern of a positive electrode active material according to an embodiment of this application; Figure 4 This is a delithiation potential plateau diagram of a lithium supplement additive according to one embodiment of this application; Figure 5 This is a delithiation potential plateau diagram of the positive electrode active material according to an embodiment of this application. Detailed Implementation

[0029] The embodiments of this application are described in detail below, with examples of these embodiments shown in the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0030] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in this application is for the purpose of describing particular embodiments only and is not intended to limit this application; unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).

[0031] The terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are open-ended expressions, meaning they include what is specified in this application but do not exclude other aspects.

[0032] In the description of this application, all figures disclosed herein, whether or not the words "approximately" or "about" are used, are approximate values. Each figure may vary by less than 10% or by a difference that is considered reasonable by one of the art, such as 1%, 2%, 3%, 4%, or 5%.

[0033] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is also expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0034] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.

[0035] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0036] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0037] In electrodeless battery systems, the positive electrode not only performs the conventional lithium storage function but also needs to provide all the lithium required to form a lithium metal anode during the initial charging process. Therefore, the positive electrode active material should possess high reversible capacity, high operating voltage, good structural stability in the delithiated state, and high electrode processing adaptability. Among these, lithium cobalt oxide, with its high compaction density, high operating voltage, and mature electrode fabrication technology, is an important material for constructing high-energy-density battery systems. In contrast, O2-phase lithium cobalt oxide exhibits different oxygen layer stacking patterns, which helps improve the structural stability of lithium cobalt oxide under high voltage and deep delithiation states, mitigating the irreversible phase transition during deep delithiation, making it an ideal positive electrode active material for electrodeless battery systems.

[0038] However, in electrodeless batteries, the active lithium is entirely derived from the positive electrode active material, resulting in a very limited internal lithium inventory. During the initial charging process, the nucleation and deposition of lithium ions on the copper foil surface typically involves a large overpotential. Furthermore, due to the insufficient lithiophilicity of the copper foil surface and uneven local current density distribution, uneven lithium deposition, dendritic lithium, or loose moss-like lithium are easily formed. These unstable lithium deposits are easily converted into electrochemically deactivated "dead lithium" during subsequent stripping, continuously inducing electrolyte decomposition and repeated formation of solid electrolyte interface films. This leads to rapid consumption of active lithium and electrolyte, causing the battery to exhibit problems such as low coulombic efficiency in the first cycle, rapid capacity decay, and short cycle life.

[0039] In a first aspect, this application proposes a battery cell comprising a positive electrode, a negative current collector, an electrolyte, and a separator disposed between the positive electrode and the negative current collector; the positive electrode comprises a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer comprising a positive electrode active material and a lithium supplementation additive, the positive electrode active material comprising O2-phase lithium cobalt oxide, and the lithium supplementation additive comprising lithium-rich cobalt-based oxide; Figure 1 As shown, the XRD pattern of the mixture of the positive electrode active material and the lithium supplementation additive has a first diffraction peak and a second diffraction peak. The peak position of the first diffraction peak is 18.35°~18.75°, the peak position of the second diffraction peak is 23.2°~23.6°, and the peak intensity ratio Q1 of the peak intensity I2 of the second diffraction peak and the peak intensity I1 of the first diffraction peak is 0.8%~10.5%.

[0040] Therefore, this application introduces O2-phase lithium cobalt oxide as the main lithium storage framework, which has a high operating voltage, high capacity, and superior structural stability. This is beneficial for improving the structural stability of the positive electrode active material under high voltage and deep delithiation conditions, mitigating irreversible phase transitions during deep delithiation, and ensuring that the increased lithium inventory from the lithium replenishment additive can be fully converted into reversible cycle capacity. Furthermore, the introduction of O2-phase lithium cobalt oxide helps improve lithium-ion insertion / extraction kinetics, reducing polarization during positive electrode delithiation, and allowing the lithium ions released from the positive electrode to better meet the needs of in-situ deposition of metallic lithium on the surface of the negative electrode current collector in a negative electrode-free system. In addition, the lithium replenishment additive can release sufficient additional active lithium during the first charge to compensate for irreversible lithium losses caused by metallic lithium nucleation and deposition on the surface of the negative electrode current collector, interface film formation, and the generation of dead lithium during cycling, thereby increasing the initial lithium inventory of the negative electrode-free lithium metal battery and extending its cycle life. Thus, the lithium replenishment effect of the lithium replenishment additive and the high-voltage stable lithium storage capacity of O2-phase lithium cobalt oxide complement each other, effectively improving the battery's energy density.

[0041] As an example, Q1 can be 0.8%, 1.5%, 2.5%, 3.5%, 4.5%, 5.5%, 6.5%, 7.5%, 8.5%, 9.5%, or 10.5%, etc. A peak intensity ratio within the aforementioned range indicates that the amount of lithium replenishing additive and positive electrode active material added is moderate, which can fully compensate for the irreversible lithium loss caused by the initial lithium metal deposition, interface film formation, and dead lithium generation; at the same time, excessive introduction of lithium replenishing additive will not lead to a decrease in the proportion of positive electrode active material, which is beneficial to improving the energy density of the battery.

[0042] In some specific examples, the first diffraction peak has an elution position of 18.35°~18.75°, which is the strongest peak of the O2 phase lithium cobalt oxide; the second diffraction peak has an elution position of 23.2°~23.6°, which is the strongest peak of the lithium supplementation additive.

[0043] In this application, the specific testing conditions for XRD are as follows: (1) Select the prepared positive electrode sheet, peel the positive electrode film from the surface of the positive electrode current collector, weigh a certain amount of powder and add it to N-methylpyrrolidone, stir for 2h~4h to dissolve the binder, filter and dry to obtain powder; (2) The powder to be tested was placed in the sample cell, compacted and leveled. A Rigaku powder X-ray diffractometer (Smartlab 9kW) was used with Cu target X-ray wavelength (1.5418462Å), tube voltage 40 kV, tube current 200 mA, scanning speed 10° / min, and scanning range 10°~90°. A one-dimensional detector (1D) was used for testing. The specific test conditions were: working temperature: 21±5℃, humidity: <65%; cooling water circulator: temperature: 23±1℃, water pressure: 0.36MPa; high pressure refrigerant: 0.8MPa~1.8MPa, low pressure refrigerant: 0.4MPa~0.7MPa; step size: 0.0200°.

[0044] The battery mentioned in the embodiments of this application can be a single physical module comprising one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in this application may include the aforementioned battery cells.

[0045] In this application, the battery cell is a negative electrode-free battery cell. A negative electrode-free battery cell typically refers to a battery cell in which no negative electrode active material layer is actively formed on the negative electrode side during the battery cell manufacturing process. For example, during the battery cell manufacturing process, no layer is formed at the negative electrode through coating or deposition processes, or a negative electrode active material layer is formed from a carbonaceous active material layer. During the first charge, ions gain electrons on the negative electrode side and deposit metal on the surface of the negative electrode current collector. During discharge, the metal can be converted back into ions and return to the positive electrode, achieving cyclic charging and discharging. Compared to other battery cells, a negative electrode-free battery cell can achieve a higher energy density because it lacks a negative electrode active material layer.

[0046] In some embodiments, Q1 is 2.0% to 8.4%. This is beneficial for further improving the energy density of the battery.

[0047] In some embodiments, the delithiation plateau of the lithium supplementation additive is 3.3 V to 3.7 V, and the delithiation plateau of the positive electrode active material is not less than 3.7 V, and optionally, 3.7 V to 4.6 V.

[0048] As an example, the delithiation platform of the lithium supplementation additive can be 3.3 V, 3.4 V, 3.5 V, 3.6 V or 3.7 V, etc., and the delithiation platform of the positive electrode active material can be 3.7 V, 3.8 V, 3.9 V, 4.0 V, 4.1 V, 4.2 V, 4.3 V, 4.4 V, 4.5 V or 4.6 V, etc.

[0049] Therefore, a suitable potential difference exists between the lithium replenishment additive and the positive electrode active material, minimizing the likelihood of side reactions between them. If the delithiation plateau of the lithium replenishment additive is too high, the lithium replenishment process must occur after the positive electrode active material has entered a higher voltage and deeper delithiation state. In this case, the lithium replenishment process is prone to superimposed on the high-voltage interface instability process of the positive electrode active material. Furthermore, an appropriate potential difference promotes a good functional division of labor between the two within the capacity contribution range. The lithium replenishment additive preferentially undergoes delithiation before the positive electrode active material, ensuring that initial lithium deposition and interface film construction in the anode-free system preferentially occur within the relatively mild positive electrode potential range. This reduces the risk of lithium ion nucleation and deposition on the anode current collector surface, rapid SEI formation, and high-delithiation interface side reactions of the positive electrode active material occurring at the same stage.

[0050] In this application, the test method for the delithiation platform of the lithium replenishment additive and the positive electrode active material is as follows: a predetermined mass of the test powder is weighed, and it is prepared into a coin cell. The assembled coin cell is then charged and discharged at 25°C with a current density of 25 mA / g, wherein the electrochemical window of the lithium replenishment additive is 2.0 V to 4.5 V (e.g., ...). Figure 4 As shown), the electrochemical window of the positive electrode active material is 3.0 V~4.6 V (e.g. Figure 5 As shown in the figure, the delithiation plateau of the material is obtained from the charge-discharge curve of the first cycle.

[0051] In some embodiments, the median particle size of the mixture of the positive electrode active material and the lithium supplementation additive is 15.6 μm to 17.8 μm.

[0052] As an example, the median particle size of the mixture of the positive electrode active material and the lithium supplementation additive can be 15.6 μm, 17.0 μm, 17.5 μm or 17.8 μm, etc.

[0053] In some embodiments, the median particle size of the positive electrode active material is 16 μm to 18 μm; and / or, the median particle size of the lithium supplementation additive is 7 μm to 8 μm.

[0054] As an example, the median particle size of the positive electrode active material can be 16 μm, 17 μm or 18 μm, etc., and the median particle size of the lithium supplementation additive can be 7 μm, 7.5 μm or 8 μm, etc.

[0055] After mixing the positive electrode active material and the lithium supplement additive, a particle size distribution is formed with the larger-diameter positive electrode active material as the main component and the smaller-diameter lithium supplement additive distributed in the interparticle spaces. Based on this, the median particle size of the mixture is further limited to 15.6 μm~17.8 μm. This ensures that the mixed particle system maintains the main framework formed by the positive electrode active material while avoiding significant agglomeration or segregation of the lithium supplement additive, thus matching the particle size of each component with the overall particle size distribution after mixing. This combination improves the dispersion uniformity and packing density of the mixed powder. Simultaneously, it reduces local enrichment or insufficient distribution of the lithium supplement additive, improves slurry stability, coating uniformity, and electrode compaction performance, and promotes the uniform release of active lithium during the first charging process, reducing local polarization, excessive lithium supplementation, and interfacial side reactions.

[0056] In this application, the method for testing the median particle size of the mixture of positive electrode active material and lithium supplementation additive is as follows: (1) Select the prepared positive electrode sheet, peel the positive electrode film from the surface of the positive electrode current collector, weigh a certain mass of powder and add it to N-methylpyrrolidone, stir for 2h~4h to dissolve the binder, filter and dry to obtain powder. Take a certain mass of powder and place it in anhydrous ethanol, add an appropriate amount of dispersant, stir evenly to obtain a suspension, sonicate and take the evenly dispersed suspension, dry it and perform scanning electron microscopy and energy dispersive spectroscopy.

[0057] (2) Based on the energy dispersive spectroscopy (EDS) results, particles that only show C element signals and do not contain Co element signals are identified as conductive agents and are not included in the statistics. The morphology of the samples was photographed from different fields of view, and the electron micrographs were analyzed using an intelligent image analysis system. A total of no less than 500 effective particles were counted, and the equivalent circle diameter of each effective particle was measured. The particle size data were arranged from smallest to largest, and the particle size corresponding to the cumulative percentage of 50% was recorded as the median particle size.

[0058] In this application, the testing methods for the median particle size of the positive electrode active material and the median particle size of the lithium supplementation additive are as follows: (1) Select the prepared positive electrode sheet, peel the positive electrode film from the surface of the positive electrode current collector, weigh a certain mass of powder and add it to N-methylpyrrolidone, stir for 2h~4h to dissolve the binder, filter and dry to obtain powder. Take a certain mass of powder and place it in anhydrous ethanol, add an appropriate amount of dispersant, stir evenly to obtain a suspension, sonicate and take the evenly dispersed suspension, dry it and perform scanning electron microscopy and energy dispersive spectroscopy.

[0059] (2) Based on the energy dispersive spectroscopy (EDS) test results, the mass content of Co and O elements measured by EDS was normalized to 100%. When the normalized mass fraction of Co was between 61wt% and 69wt%, the particles were determined to be positive electrode active materials; when the normalized mass fraction of Co was between 44wt% and 52wt%, the particles were determined to be lithium supplementary additives. The morphology of the samples was photographed from different fields of view, and the electron microscope images were analyzed. At least 500 effective particles were counted, and the equivalent circle diameter of each effective particle was measured. The particle size data were arranged from smallest to largest, and the particle size corresponding to the cumulative percentage of 50% was recorded as the median particle size of the two materials.

[0060] In some embodiments, the chemical formula of the positive electrode active material is LiCo. p M q O2, wherein M includes at least one of Zn, Ni, Mg, Cu, and Ca, 0.9≤p≤1.0, 0≤q≤0.1, and p+q=1.0. Therefore, doping with element M helps improve the cycle stability of the positive electrode active material under high voltage.

[0061] As an example, p can be 0.9, 0.92, 0.94, 0.96, 0.98 or 1.0, etc., and q can be 0, 0.02, 0.04, 0.06, 0.08 or 0.1, etc.

[0062] In some embodiments, the lithium supplementation additive comprises a matrix and a manganese-based oxide located on at least a portion of the surface of the matrix, the matrix having the chemical formula Li. x Co y E z O4, wherein E includes at least one of Zn, Mg, Cu, and Ca, 5.9≤x≤6.15, 0.9≤y≤1.0, 0≤z≤0.1, y+z=1.0. Therefore, manganese-based oxides can stabilize the surface of lithium-replenishing additives, effectively improving the environmental stability of the additives while mitigating side reactions such as active oxygen release and electrolyte oxidation decomposition during the first charging process, reducing unnecessary consumption of active lithium. Furthermore, manganese-based oxides possess certain variable valence state characteristics, which, under controlled conditions, can assist in constructing an interface environment conducive to lithium nucleation, reducing the tendency for uneven local deposition on the negative electrode side. Simultaneously, the residual phase after lithium removal from the lithium-replenishing additive is compatible with the O2 phase lithium cobalt oxide. Specifically, the Li-Co-O / Co-O residual phase formed after lithium removal from the additive belongs to the same cobalt oxide system as the O2 phase lithium cobalt oxide, exhibiting high compatibility in elemental composition and oxygen coordination environment, which can reduce local impedance concentration and side reaction active sites caused by heterogeneous residual phases.

[0063] As an example, x can be 5.9, 5.95, 6.0, 6.05, 6.1 or 6.15, etc.; y can be 0.9, 0.92, 0.94, 0.96, 0.98 or 1.0, etc.; and z can be 0, 0.02, 0.04, 0.06, 0.08 or 0.1, etc.

[0064] In some embodiments, the manganese-based oxide includes at least one selected from MnO, Mn2O3, Mn3O4, MnO2, LiMnO2, Li2MnO3, and LiMn2O4. This helps to further improve the air stability of the lithium supplementation additive, reduce unnecessary consumption of active lithium, and decrease the tendency for uneven local deposition on the negative electrode side.

[0065] In some embodiments, the mass content of Mn element in the mixture of the positive electrode active material and the lithium supplementation additive is 0.0005wt% to 0.1wt%, and optionally 0.001% to 0.077%.

[0066] As an example, the mass content of Mn element in the mixture of the positive electrode active material and the lithium supplementation additive can be 0.0005wt%, 0.0008wt%, 0.001wt%, 0.002wt%, 0.005wt%, 0.01wt%, 0.02wt%, 0.05wt%, or 0.1wt%, etc.

[0067] This helps to create an interface environment conducive to lithium metal nucleation and reduces the tendency for uneven local deposition on the negative electrode side.

[0068] In this application, the mass content of Mn element in the mixture of positive electrode active material and lithium supplementation additive is determined by inductively coupled plasma optical emission spectrometry (ICP-OES). Specifically, an appropriate amount of the mixture of positive electrode active material and lithium supplementation additive is weighed into a specific solvent for digestion. After the sample is completely dissolved, the test solution is obtained. A standard curve is established using a Mn standard solution, the concentration of Mn element in the test solution is determined, and the mass fraction of Mn element in the test sample is calculated based on the sample weight, final volume, and dilution factor. Each sample is tested in triplicate, and the final result is the average value.

[0069] In some embodiments, such as Figure 2 As shown, the XRD pattern of the lithium supplement additive has a third diffraction peak. The peak intensity ratio Q2 of the third diffraction peak I3 to the peak intensity I2 of the second diffraction peak satisfies 0 < Q2 ≤ 3.5%, and Q2 can be selected from 0.5% to 3.0%.

[0070] As an example, Q2 can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or 3.5%, etc.

[0071] When the peak intensity ratio is within the above range, it indicates that the coating amount of manganese-based oxide on the surface of the lithium supplement additive is moderate, which helps to build an interface environment conducive to the nucleation of metallic lithium and reduces the tendency of uneven local deposition on the negative electrode side.

[0072] In this application, the XRD pattern testing method for the lithium supplementation additive is as follows: (1) Select the prepared positive electrode sheet, peel the positive electrode film from the surface of the positive electrode current collector, weigh a certain amount of powder and add it to N-methylpyrrolidone, stir for 2h~4h to dissolve the binder, filter and dry to obtain powder; (2) The mixed powder was sequentially sieved through precision sieves with pore sizes of 15 μm and 10 μm. The oversize particles with a particle size greater than 15 μm were enriched O2 phase lithium cobalt oxide, the oversize particles with a particle size of 10 μm to 15 μm were used as transition components, and the undersize particles with a particle size less than 10 μm were enriched lithium supplementation additives. The lithium supplementation additive enrichment components with a particle size less than 10 μm were taken, and their composition was confirmed by SEM-EDS before XRD testing was performed. (3) The obtained lithium-supplementing additive powder was placed in the sample cell, compacted and spread. A Rigaku powder X-ray diffractometer (Smartlab 9kW) was used with Cu target X-ray wavelength (1.5418462Å), tube voltage 40 kV, tube current 200 mA, scanning speed 10° / min, and scanning range 10°~90°. A one-dimensional detector (1D) was used for testing. The specific test conditions were: working temperature: 21±5℃, humidity: <65%; cooling water circulator: temperature: 23±1℃, water pressure: 0.36MPa; high pressure refrigerant: 0.8MPa~1.8MPa, low pressure refrigerant: 0.4MPa~0.7MPa; step size: 0.0200°.

[0073] In some specific examples, the third diffraction peak is a characteristic peak of manganese-based oxides, with peak positions of 15.0°~15.8°, 18.1°~18.9°, 21.2°~21.9°, 31.6°~36.6°, or 39.8°~41.3°.

[0074] In some embodiments, the mass fraction of the manganese-based oxide in the lithium replenishing additive is 0.1% to 4.3%, for example, it can be 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, or 4.3%. This helps to improve the interfacial stability of the lithium replenishing additive and reduce the occurrence of side reactions such as the release of reactive oxygen species and the oxidative decomposition of the electrolyte during the first charging process.

[0075] In some embodiments, the mass fraction of the positive electrode active material in the positive electrode film layer is 90% to 97%, for example, it can be 90%, 91%, 92%, 93%, 94%, 95%, or 97%. This is beneficial for improving the battery's capacity utilization and cycle stability.

[0076] In some embodiments, the mass ratio of the lithium replenishing additive to the positive electrode active material in the positive electrode film layer is (0.5~5):100, for example, it can be 0.5:100, 1:100, 2:100, 3:100, 4:100 or 5:100, etc.; it can be selected as (1~4):100. Therefore, by adding an appropriate amount of lithium replenishing additive, the irreversible lithium loss caused by the initial lithium metal deposition, interface film formation and dead lithium generation can be fully compensated; at the same time, the proportion of positive electrode active material will not decrease due to excessive introduction of lithium replenishing additive, which is beneficial to improving the energy density of the battery.

[0077] In some embodiments, the positive electrode film further includes a conductive agent and a binder; wherein the conductive agent includes at least one selected from carbon nanotubes, graphene, acetylene black, and Ketjen black; and the binder includes at least one selected from polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, and styrene-butadiene rubber. This improves the conductivity of the positive electrode film.

[0078] In some embodiments, the negative electrode current collector includes at least one of copper foil, carbon-coated copper foil, and perforated copper foil. This helps to enhance the affinity for lithium, reduce interfacial resistance, decrease local current density, make lithium ion distribution more uniform, and suppress lithium dendrite growth.

[0079] In some embodiments, the membrane comprises a ceramic particle-modified polyethylene microporous membrane. This improves the mechanical strength of the membrane and effectively resists lithium dendrite penetration.

[0080] In some embodiments, the electrolyte is ethylene carbonate (EC), diethyl carbonate (DEC), and LiPF6, wherein the volume ratio of ethylene carbonate (EC) to diethyl carbonate (DEC) is 3:7, and the concentration of LiPF6 is 1 mol / L.

[0081] As an example, the preparation methods of a single battery cell include: A positive electrode slurry is prepared by mixing O2 phase lithium cobalt oxide, lithium supplementation additive, conductive agent, binder and organic solvent. The positive electrode slurry is coated on at least one side of the positive electrode current collector and dried to obtain a positive electrode sheet. The positive electrode, separator, and negative electrode current collector are stacked and wound to obtain a bare cell. After injecting electrolyte, the cell is packaged to obtain the negative electrode-free lithium metal battery.

[0082] In a second aspect, this application proposes a method for preparing the aforementioned positive electrode active material, resulting in a positive electrode active material with high capacity and structural stability. The preparation method is simple, easy to operate, and readily applicable to industrial production. Specifically, the method includes: S1: The cobalt source, sodium source and optional M source are mixed and sintered in an oxygen atmosphere, then crushed and sieved to obtain the P2 phase precursor.

[0083] In some embodiments, the cobalt source includes at least one of cobalt tetroxide, cobalt hydroxide, cobalt suboxide, cobalt nitrate, cobalt sulfate, and cobalt hydroxyoxide; the sodium source includes at least one of sodium carbonate, sodium bicarbonate, and sodium hydroxide; and the M source includes at least one of the oxides and hydroxides corresponding to the element M.

[0084] In some embodiments, the ratio z of the sum of the molar amounts of sodium in the sodium source, cobalt in the cobalt source, and M in the M source is n(Na):n(Co+M), where 0.7 ≤ z < 1, and can be, for example, 0.7, 0.75, 0.8, 0.85, 0.9, or 0.99.

[0085] In some embodiments, the crushing method includes at least one of ball milling, sand milling, air jet milling, and colloid milling.

[0086] In some embodiments, the sieving is performed using a 200-400 mesh sieve.

[0087] S2: The P2 phase precursor is immersed in a mixed aqueous solution of LiCl and LiOH for reaction, and then filtered, washed and dried to obtain the positive electrode active material, which is O2 phase lithium cobalt oxide.

[0088] In some embodiments, the concentration of the mixed aqueous solution of LiCl and LiOH is 1.0 mol / L to 3.0 mol / L, for example, it can be 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L or 3.0 mol / L.

[0089] In some embodiments, the reaction time is 20h~30h (e.g., 20h, 22h, 24h, 26h, 28h or 30h, etc.), and the temperature is 100℃.

[0090] In some embodiments, the drying temperature is 50°C to 90°C (e.g., 50°C, 60°C, 70°C, 80°C, or 90°C).

[0091] Meeting the above conditions helps to prepare positive electrode active materials with stable structure, high purity, and appropriate particle size.

[0092] In some embodiments, the sintering temperature is 700℃~800℃ (e.g., 700℃, 720℃, 740℃, 760℃, 780℃, or 800℃), and the holding time is 40h~50h (e.g., 40h, 42h, 44h, 46h, 48h, or 50h). This helps to synthesize a high-purity, structurally stable P2 phase precursor.

[0093] In a third aspect, this application proposes a method for preparing the aforementioned lithium-replenishing additive. This method involves coating a substrate surface with a manganese-based oxide to obtain a lithium-replenishing additive with high air stability. Specifically, the method includes: S10: The lithium source, cobalt source and optional E source are mixed and subjected to the first sintering treatment in an inactive atmosphere. After crushing and sieving, the matrix is ​​obtained.

[0094] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, and lithium chloride; the cobalt source includes at least one of cobalt oxide and cobalt hydroxide; and the E source includes at least one of the oxide and hydroxide corresponding to element E.

[0095] In some embodiments, the ratio of the molar amounts of lithium in the lithium source to the sum of the molar amounts of cobalt in the cobalt source and E in the E source, n(Li):n(Co+E), is (5.9~6.15):1, for example, it can be 5.9, 6.0, 6.1 or 6.15, etc.

[0096] In some embodiments, the mixing equipment may be a high-frequency mixer or a hummingbird resonance.

[0097] In some embodiments, the temperature of the first sintering treatment is 500℃~1000℃ (e.g., 500℃, 600℃, 700℃, 800℃, 900℃, or 1000℃), and the time is 8h~24h (e.g., 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, or 24h). This helps to obtain pure-phase Li. x Co y E z O4 matrix.

[0098] In some embodiments, the atmosphere of the first sintering treatment is nitrogen or argon, and the equipment used may be a tube furnace, a box furnace, a pusher kiln, or a roller kiln.

[0099] In some embodiments, the crushing method includes at least one of ball milling, sand milling, air jet milling, and colloid milling.

[0100] In some embodiments, the sieving is performed using a 200-400 mesh sieve.

[0101] S20: The matrix is ​​mixed with a manganese source and then subjected to a second sintering treatment under an inactive atmosphere to form manganese-based oxides on a portion of the surface of the matrix. After crushing and sieving, the lithium supplementation additive is obtained.

[0102] In some embodiments, the manganese source includes at least one of MnO, Mn2O3, Mn3O4, and MnO2.

[0103] In some embodiments, the mixing device is a hummingbird resonance with a resonance frequency of 55 Hz, an acceleration of 40 G to 100 G, and a resonance time of 20 min to 80 min.

[0104] In some embodiments, the temperature of the second sintering treatment is 300℃~700℃ (e.g., 300℃, 400℃, 500℃, 600℃ or 700℃, etc.), and the time is 5h~10h (e.g., 5h, 6h, 7h, 8h, 9h or 10h, etc.).

[0105] In some embodiments, the atmosphere for the second sintering process is nitrogen or argon, and the equipment used may be a tube furnace, a box furnace, a pusher kiln, or a roller kiln.

[0106] In some embodiments, the crushing method includes at least one of ball milling, sand milling, air jet milling, and colloid milling.

[0107] In some embodiments, the sieving is performed using a 200-400 mesh sieve.

[0108] Meeting the above conditions helps to form a dense and uniform manganese-based oxide on the substrate surface, which in turn helps to improve the air stability of the lithium supplement additive.

[0109] The description of the various embodiments above tends to emphasize the differences between the various embodiments. The similarities or similarities between them can be referred to, and for the sake of brevity, they will not be repeated here.

[0110] The following specific embodiments illustrate the solution of this application. It should be noted that these embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0111] Example 1 (1) Preparation of positive electrode active material: Cobalt source (cobalt tetroxide) and sodium source (sodium carbonate) are mixed evenly in a specific ratio, sintered in a tube furnace under an oxygen atmosphere, crushed, and sieved through a 300-mesh sieve to obtain the P2 phase precursor. A mixed aqueous solution of LiCl and LiOH at a specific concentration was prepared. The P2 phase precursor was immersed in the mixed solution for reaction. Subsequently, the solution was filtered, washed, and dried to obtain O2 phase lithium cobalt oxide. The XRD pattern of the O2 phase lithium cobalt oxide is shown below. Figure 3 As shown.

[0112] (2) Preparation of lithium supplementation additives: The lithium source (lithium oxide) and cobalt source (cobalt suboxide) are mixed evenly according to the molar ratio in the chemical formula, and the first sintering treatment is carried out in a tube furnace under a nitrogen atmosphere. After crushing and sieving through a 300-mesh sieve, the matrix is ​​obtained. The matrix and manganese source (Mn3O4) are mixed evenly at a specific mass ratio, and a second sintering treatment is carried out in a tube furnace under a nitrogen atmosphere. After crushing and sieving through a 300-mesh sieve, a lithium supplement additive is obtained.

[0113] (3) Weigh and mix O2 phase lithium cobalt oxide, lithium supplementation additive, acetylene black and PVDF in a mass ratio of 94.05:0.95:2.5:2.5. Add all raw materials to N-methylpyrrolidone to make a slurry, coat it on aluminum foil, and dry it to obtain the positive electrode sheet. (4) The negative electrode current collector uses a copper foil current collector; (5) The diaphragm is a ceramic particle modified polyethylene (PE) microporous diaphragm; the electrolyte is ethylene carbonate (EC), diethyl carbonate (DEC) and LiPF6, wherein the volume ratio of ethylene carbonate (EC) and diethyl carbonate (DEC) is 3:7 and the concentration of LiPF6 is 1 mol / L. (6) Assemble the positive electrode, separator and negative current collector using a button cell, add electrolyte and let stand for 10 hours, then complete the battery cycle.

[0114] Comparative Example 2 The difference from Example 1 is that the lithium supplementing additive is replaced with Li5FeO4, and the preparation method of Li5FeO4 is as follows: Lithium source (lithium oxide) and iron source (Fe2O3) were mixed evenly at a molar ratio of 5:1 and heat-treated in a tube furnace under a nitrogen atmosphere at a temperature of 600℃ for 16 hours. The mixture was then crushed and sieved through a 300-mesh sieve to obtain Li5FeO4.

[0115] Comparative Example 5 The difference from Example 1 is that the O2 phase lithium cobalt oxide is replaced with the O3 phase lithium cobalt oxide.

[0116] The differences between other embodiments and comparative examples and embodiment 1 are shown in the table below.

[0117] Table 1-1 Preparation methods of positive electrode active materials

[0118] Table 1-2 Preparation methods of lithium supplementation additives

[0119] Table 2-1

[0120] Table 2-2

[0121] Table 2-3

[0122] For the relevant tests listed in Tables 2-1 to 2-3, please refer to the aforementioned instruction manual.

[0123] The batteries prepared above were subjected to the following tests, and the test results are shown in Table 3.

[0124] (1) First week charge specific capacity: The assembled coin cell was charged and discharged at 25°C with a current density of 25 mA / g, where the electrochemical window was 3.0 V~4.6 V, and the first week charge specific capacity was read from the test software.

[0125] (2) First-cycle discharge specific capacity: The assembled coin cell was charged and discharged at 25°C with a current density of 25 mA / g, where the electrochemical window was 3.0 V to 4.6 V, and the first-cycle discharge specific capacity was read from the test software.

[0126] (3) Cycling performance: The assembled coin cells were charged and discharged at 25°C with a current density of 25 mA / g, where the electrochemical window was 3.0 V to 4.6 V. The battery cycle performance was read from the test software.

[0127] (4) Capacity recovery rate: The assembled coin cells were charged and discharged at 25°C with current densities of 25 mA / g, 50 mA / g, 125 mA / g, 250 mA / g, and 500 mA / g, respectively, for two cycles at each rate. After each cycle, the charge and discharge current density was restored to 25 mA / g and the cycle was repeated twice. The discharge specific capacity of the second cycle at the initial 25 mA / g current density was recorded as P1, and the discharge specific capacity of the last cycle after restoring to 25 mA / g current density was recorded as P2. The capacity recovery rate R was calculated according to the following formula: R = P2 / P1 × 100%. The higher the capacity recovery rate, the better the reversible capacity retention capability of the battery after being charged and discharged at a higher rate to a lower rate.

[0128] Table 3

[0129] As can be seen from the table above, the introduction of O2 phase lithium cobalt oxide and lithium replenishment additives into the cathode film layer in this application is beneficial to improving the structural stability of the cathode active material under high voltage and deep delithiation state, and extending the battery cycle life; at the same time, controlling the amount of additives within the limits of this application can fully compensate for the irreversible lithium loss caused by the initial lithium metal deposition, interface film formation and dead lithium generation; and the introduction of excessive lithium replenishment additives will not lead to a decrease in the proportion of cathode active material, which is beneficial to improving the energy density of the battery.

[0130] In Comparative Example 1, no lithium additive was added, and the active lithium in the battery came entirely from the positive electrode active material, resulting in a very limited lithium inventory within the system. During the first charge, the nucleation and deposition of lithium ions on the copper foil surface typically involves a large overpotential. Furthermore, due to the insufficient lithiophilicity of the copper foil surface and uneven local current density distribution, uneven lithium deposition, dendritic lithium, or loose moss-like lithium are easily formed, causing the battery to exhibit rapid capacity decay and short cycle life.

[0131] Comparative Example 2 uses Li5FeO4 as the lithium supplement additive. It has poor compatibility with O2 phase lithium cobalt oxide in terms of elemental composition and electrochemical environment. In addition, Li5FeO4 has a low charge specific capacity. In practical applications, it also has problems such as insufficient air stability, more residual alkaline substances, and gas release during charging, resulting in poor battery capacity performance and cycle stability.

[0132] In Comparative Example 3, Q1 is too small, making it difficult for the lithium replenishment additive to fully compensate for the irreversible lithium loss caused by the initial lithium metal deposition, interface film formation, and dead lithium generation, thus affecting the battery's capacity performance.

[0133] In Comparative Example 4, Q1 was too large, resulting in a smaller amount of positive electrode active material added, which affected the battery's capacity utilization and capacity recovery rate.

[0134] Comparative Example 5 uses O3 phase lithium cobalt oxide as the positive electrode active material, which is structurally unstable under high voltage, thus deteriorating the battery's capacity utilization and cycle stability.

[0135] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, characterized in that, The device includes a positive electrode, a negative current collector, an electrolyte, and a separator disposed between the positive electrode and the negative current collector. The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material and a lithium supplementation additive. The positive electrode active material includes O2-phase lithium cobalt oxide, and the lithium supplementation additive includes lithium-rich cobalt-based oxide. In the XRD pattern of the mixture of the positive electrode active material and the lithium supplementation additive, there are a first diffraction peak and a second diffraction peak. The elution position of the first diffraction peak is 18.35°~18.75°, and the elution position of the second diffraction peak is 23.2°~23.6°. The peak intensity ratio Q1 of the second diffraction peak I2 and the first diffraction peak I1 is 0.8%~10.5%.

2. The battery cell according to claim 1, characterized in that, Q1 ranges from 2.0% to 8.4%.

3. The battery cell according to claim 1 or 2, characterized in that, The lithium replenishment additive has a delithiation plateau of 3.3V to 3.7V, and the positive electrode active material has a delithiation plateau of not less than 3.7V, and optionally 3.7V to 4.6V.

4. The battery cell according to claim 1 or 2, characterized in that, The median particle size of the mixture of the positive electrode active material and the lithium supplementation additive is 15.6 μm to 17.8 μm.

5. The battery cell according to claim 4, characterized in that, The median particle size of the positive electrode active material is 16 μm to 18 μm; and / or, The median particle size of the lithium supplement additive is 7 μm to 8 μm.

6. The battery cell according to claim 1 or 2, characterized in that, The chemical formula of the positive electrode active material is LiCo. p M q O2, wherein M includes at least one of Zn, Ni, Mg, Cu, and Ca, 0.9≤p≤1.0, 0≤q≤0.1, and p+q=1.

0.

7. The battery cell according to claim 1 or 2, characterized in that, The lithium supplement additive comprises a matrix and a manganese-based oxide located on at least a portion of the surface of the matrix, wherein the chemical formula of the matrix is ​​Li. x Co y E z O4, wherein E includes at least one of Zn, Mg, Cu, and Ca, 5.9≤x≤6.15, 0.9≤y≤1.0, 0≤z≤0.1, and y+z=1.

0.

8. The battery cell according to claim 7, characterized in that, The manganese-based oxide includes at least one of MnO, Mn2O3, Mn3O4, MnO2, LiMnO2, Li2MnO3, and LiMn2O4.

9. The battery cell according to claim 7, characterized in that, The mass content of Mn element in the mixture of the positive electrode active material and the lithium supplementation additive is 0.0005wt%~0.1wt%, and can be selected as 0.001%~0.077%.

10. The battery cell according to claim 9, characterized in that, The XRD pattern of the lithium supplement additive has a third diffraction peak. The peak intensity ratio Q2 of the third diffraction peak I3 to the peak intensity I2 of the second diffraction peak satisfies 0 < Q2 ≤ 3.5%, and Q2 can be selected from 0.5% to 3.0%.

11. The battery cell according to claim 7, characterized in that, The mass fraction of the manganese-based oxide in the lithium supplement additive is 0.1% to 4.3%.

12. The battery cell according to claim 1 or 2, characterized in that, The mass fraction of the positive electrode active material in the positive electrode film layer is 90%~97%.

13. The battery cell according to claim 1 or 2, characterized in that, The mass ratio of the lithium supplementation additive to the positive electrode active material in the positive electrode film layer is (0.5~5):100, and can be selected as (1~4):

100.

14. The battery cell according to claim 1 or 2, characterized in that, The positive electrode film layer further includes a conductive agent and a binder; wherein the conductive agent includes at least one of carbon nanotubes, graphene, acetylene black, and Ketjen black; the binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, and styrene-butadiene rubber; and / or, The negative electrode current collector includes at least one of copper foil, carbon-coated copper foil, and perforated copper foil; and / or, The diaphragm comprises a polyethylene microporous diaphragm modified with ceramic particles.

15. A method for preparing a positive electrode active material, characterized in that, include: The cobalt source, sodium source and optional M source are mixed and sintered in an oxygen atmosphere, then crushed and sieved to obtain the P2 phase precursor. The P2 phase precursor was immersed in a mixed aqueous solution of LiCl and LiOH for reaction, and then filtered, washed and dried to obtain the positive electrode active material, which is O2 phase lithium cobalt oxide.

16. The method according to claim 15, characterized in that, At least one of the following conditions must be met: The cobalt source includes at least one of cobalt tetroxide, cobalt hydroxide, cobalt sulfide, cobalt nitrate, cobalt sulfate, and cobalt hydroxyoxide. The sodium source includes at least one of sodium carbonate, sodium bicarbonate, and sodium hydroxide; The ratio z of the molar amounts of sodium in the sodium source to the sum of the molar amounts of cobalt in the cobalt source and M in the M source is n(Na):n(Co+M), 0.7≤z<1; The M source includes at least one of the oxides and hydroxides corresponding to the M element; The sintering temperature is 700℃~800℃, and the holding time is 40h~50h; The concentration of the mixed aqueous solution of LiCl and LiOH is 1.0 mol / L to 3.0 mol / L; The reaction time is 20-30 hours, and the temperature is 100°C. The drying temperature is 50℃~90℃.

17. A method for preparing a lithium supplement additive, characterized in that, include: The lithium source, cobalt source and optional E source are mixed and subjected to a first sintering treatment in an inactive atmosphere. The matrix is ​​then crushed and sieved. The matrix is ​​mixed with a manganese source and then subjected to a second sintering treatment under an inactive atmosphere to form manganese-based oxides on a portion of the surface of the matrix. After crushing and sieving, the lithium supplement additive is obtained.

18. The method according to claim 17, characterized in that, At least one of the following conditions must be met: The lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, and lithium chloride; The cobalt source includes at least one of cobalt oxide and cobalt hydroxide; The E source includes at least one of the oxides and hydroxides corresponding to the element E; The manganese source includes at least one of MnO, Mn2O3, Mn3O4, and MnO2; The ratio of the molar amounts of lithium in the lithium source to the sum of the molar amounts of cobalt in the cobalt source and E in the E source, n(Li):n(Co+E), is (5.9~6.15):1; The temperature of the first sintering treatment is 500℃~1000℃, and the time is 8h~24h; The second sintering treatment is performed at a temperature of 300℃ to 700℃ for 5 hours to 10 hours.